Models of constant user informational interests knowledge representation in informational retrieval systems - Рогушина, Ю.В. (Proceedings of National Aviation University (archive), 2004)
Ontological approach to sphere of user`s informational interests formalization for effectiveness increasing of informational retrieval results is proposed.